Where Is Linz’S Gridlock? Salvador Allende and the Success of Presidential Bills in Chile, 1958–1973 - Osorio-Flores, R (Routledge, 2025)
We study the success of presidential bills in Chile between 1958 and 1973 and disprove the claim, made by Linz and others, in the debate on the perils of presidentialism, that Salvador Allende (1970–1973) suffered from legislative paralysis. We revise the 1113 bills introduced by presidents Jorge Alessandri (1958–1964), Eduardo Frei (1964–1970) and Allende, and identified those enacted. Allende had a lower success rate but introduced more bills than Frei or Alessandri and, by the time his term abruptly ended, had enacted more laws than his predecessors. Changes to lawmaking rules likely induced Allende to introduce more bills than his predecessors. While presidentialism might have its perils, especially for minority presidents, Allende did not experience legislative gridlock when compared to other Chilean presidents. Although some key Allende bills failed to pass, especially in the last year, the opposition-controlled Congress passed some Allende bills even in the weeks before his overthrow. © 2023 Informa UK Limited, trading as Taylor & Francis Group.